Causes of Mortality for Endangered Antillean Manatees in Cuba - Alvarez-Alemán, Anmari; García Alfonso, Eddy; Powell, James A.; Jacoby, Charles A.; Austin, James D.; Frazer, Thomas K. (Frontiers in Marine Science, 2021)
The Antillean manatee is categorized as endangered by the IUCN primarily due to its low abundance. Further declines in abundance are expected due to a group of human related threats that include illegal hunting, fatal interactions with fishing gear, increasing watercraft traffic, and pollution. The nature of current threats is not well described for every critical population of manatees. In particular, threats to manatees have not been documented or evaluated in a systematic manner in coastal waters surrounding Cuba, which is a major reason why plans specifically addressing conservation of manatees in Cuba have not been implemented. To address this lack of information, we assessed patterns in various threats by reviewing reports of stranded (alive or dead) and captured manatees, with some reports being historical and others consistently available since 2001. For 94% of the contemporary cases, carcasses of dead animals were reported; the remainder (6%) involved live manatees and subsequent efforts to rescue and rehabilitate them. Documented causes of mortality included poaching (38%), entanglement in fishing gear (10%), deaths of dependent calves (2.5%), and boat collisions (2.5%). The cause of death for the remaining 47% of reports could not be determined. Mortalities were highest in areas with intensive commercial fishing effort, and mortalities in marine protected areas indicated a need for improved management. These initial findings provide the first estimates of the magnitude of mortality of manatees in Cuba and yield valuable insights into the causes of deaths. The existence of intense and poorly regulated fishing in certain areas, including protected areas, represents a potentially significant threat to manatees. The effects and management of this activity, especially in habitats that are critical for manatees, merit further attention.